التقييم المكاني للتعليم الابتدائي في قضاء الإمام الصادق - Shamel Jabbar Al-Mansouri , Assist. Lect . Diaa (Basra studies journal, 2026)
This study examines the reality of primary education in Imam al-Sadiq district of Basra Governorate for identifying the most prominent challenges facing education there. These challenges reflect the gap between rapid population growth and available infrastructure. The research also assesses the extent to which these educational institutions meet local standards. Furthermore, it focuses on identifying obstacles hindering the educational process in these schools and proposing appropriate solutions in accordance with the standards of the Iraqi Ministry of Education and the Ministry of Planning. The district faces a significant shortage of school buildings, leading to the adoption of double and triple shifts in some schools. Overcrowding is also a major issue, with some classes exceeding 50 students, making effective classroom management and instruction difficult. The research also addresses the issue of prefabricated schools, which are inadequate and have been used for an extended period as a temporary measure. The reality of education in the district of Imam Al-Sadiq requires serious action from government agencies to increase financial allocations for building new schools, and to transform mud and caravan schools into solid buildings, with the need to provide schools with modern technologies to keep pace with educational development.